Influences of environmental relative humidity and temperature on Si/Carbon/Ge tribovoltaic electrical generator - Xiang, Lingxi (Nanyang Technological University, 2025)
Over the past few years, there has been growing interest in tribovoltaic nano- generators (TVNGs) due to their ability to convert mechanical energy into di- rect current (DC) electricity through friction-induced charge transfer. This thesis utilises a semiconductor wire-based power generators to convert ultrasonic vibra- tions into electric output, using two dynamic semiconductor wires/metal junc- tions. The influence of humidity and temperature on the electrical output of the devices consisting of semiconductor wires embedded in carbon cloth were also explored. The results show that the current output is non-linearly related to humidity. In addition, at a constant humidity, an increase in temperature leads to a sustained increase in current output, which may be due to thermal-assisted carrier excitation and potential thermoelectric effects. These findings provide new insights into the environmental adaptation of tribo- voltaic nanogenerators, and understanding these mechanisms is crucial for opti- mising TVNGs under different atmospheric conditions and advancing their appli- cations in self-powered electronics, energy harvesting and environmental sensing.